THE EXISTENCE OF URGENCY AND RELIGIOUS CULTURE IN ACHIEVING THE OBJECTIVE OF EDUCATION IN SCHOOLS - Iswantir Muhamad (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2017)
Culture is the result of creativity, taste, and works created by society, which are complex and derived from knowledge, belief, art, morals, law, custom, including the skills and habits that runs on society. Human beings is a social creature whose role is not only become the producers of systems thinking, values, morals, norms, and conviction but also social interaction with another human beings and the nature of life. Humans are governed by systems of thinking, values, morals, norms, and beliefs that have been generated in the community. Education is a planned effort to develop the potency of learners, so that they have a system of thinking, values, morals, and beliefs that inherited by their community and develop the appropriate life guideance for present and the future. In the process of cultural education and the character of the nation; active participant or learners that develop their potency, the internalization process, and appreciation of values into their personalities in the mix in society,help develop the community life become more prosperous , and develop the nation's dignity. The existence and urgency of creating a culture and a religiousity in school actually is a process of the familiarization or habituation of values of Islamic education in schools, so as to improve and strengthen the educational goals. Budaya adalah hasil cipta, rasa, dan karya yang dibuat oleh masyarakat yang bersifat kompleks bersumber dari pengetahuan, kepercayaan, seni, moral, hukum, adat-istiadat, serta kemampuan-kemampuan dan kebiasaan-kebiasaan yang berjalan pada masyarakat. Manusia sebagai makhluk sosial menjadi penghasil sistem berpikir, nilai, moral, norma, dan keyakinan; akan tetapi juga dalam interaksi dengan sesama manusia dan alam kehidupan, manusia diatur oleh sistem berpikir, nilai, moral, norma, dan keyakinan yang telah dihasilkannya. Religiusitas lebih melihat aspek yang “di dalam lubuk hati nurani” pribadi, sikap personal yang sedikit banyak misteri bagi orang lain, karena menapaskan intimitas jiwa, cita rasa yang mencakup totalitas ke dalam si pribadi manusia. Pendidikan merupakan upaya terencana dalam mengembangkan potensi peserta didik, sehingga mereka memiliki sistem berpikir, nilai, moral, dan keyakinan yang diwariskan masyarakatnya dan mengembangkan warisan tersebut ke arah yang sesuai untuk kehidupan masa kini dan masa mendatang. Dalam proses pendidikan budaya dan karakter bangsa, secara aktif peserta didik mengembangkan potensi dirinya, melakukan proses internalisasi, dan penghayatan nilai- nilai menjadi kepribadian mereka dalam bergaul di masyarakat, mengembangkan kehidupan masyarakat yang lebih sejahtera, serta mengembangkan kehidupan bangsa yang bermartabat. Eksistensi dan urgensi penciptaan budaya religius di sekolah sesungguhnya adalah pembudayaan atau pembiasaan nilai-nilai pendidikan agama Islam dalam kehidupan di sekolah, sehingga dapat meningkatkan dan menguatkan tujuan pendidikan.